Education System in UK and USA - G'aniyeva, Hayriniso (Maktabgacha taʼlim jurnali, 2023)
First, education is compulsory in all countries (Moos, 2013, 12). Thus all children from the age of four to eighteen must attend both elementary, primary and secondary schools. They both believe that the basic education is crucial to students between the mentioned ages as it directs them into choosing their desired careers in future. Another similarity is that both education systems are funded by the government apart from the private schools